2004
DOI: 10.1152/ajpheart.01083.2003
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin inhibitor reduces myocardial infarction in apoE−/−× LDLR−/−mice

Abstract: We have previously shown that atherosclerotic apolipoprotein E-deficient (apoE(-/-)) x LDL receptor-deficient (LDLR(-/-)) mice develop myocardial infarction when exposed to hypoxic stress. This study was performed to assess the role of thrombin and thrombosis in this process. ApoE(-/-) x LDLR(-/-) mice were fed a cholesterol-rich diet for 8 mo and were then subjected to hypoxic stress while receiving isoflurane anesthesia. One group received a bolus dose (5.6 micromol/kg) of the thrombin inhibitor melagatran, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
(40 reference statements)
2
12
0
Order By: Relevance
“…Marked reduction in plaque size was reported when mice were treated with the thrombin inhibitor dabigatran (181). Similar results were reported with another thrombin inhibitor, melagatran (117,746). Several other genes that affect clotting or platelet activity are also reviewed in TABLE 10.…”
Section: B Thrombosis and Atherosclerosissupporting
confidence: 64%
“…Marked reduction in plaque size was reported when mice were treated with the thrombin inhibitor dabigatran (181). Similar results were reported with another thrombin inhibitor, melagatran (117,746). Several other genes that affect clotting or platelet activity are also reviewed in TABLE 10.…”
Section: B Thrombosis and Atherosclerosissupporting
confidence: 64%
“…Hemdahl et al reported protective effects of sc melagatran in a mouse model of hypoxic stress induced myocardial infarction. 24 In the present study, we show for the first time that oral administration of melagatran attenuated the progression of ath- erosclerotic plaques in brachiocephalic arteries of apoEϪ/Ϫ mice. Melagatran had beneficial effects on both size and composition of the advanced atherosclerotic lesions.…”
Section: Discussionsupporting
confidence: 53%
“…We have previously demonstrated that stress can induce MI in atherosclerotic mice (Caligiuri et al 1999, Hemdahl et al 2004). Our present data show that the stress challenge triggers a process with cardiac instability which leads to irreversible ischaemia and MI.…”
Section: Discussionmentioning
confidence: 99%
“…While the initiation and early stages of progression of atherosclerosis have been widely investigated, the complications leading to myocardial infarction (MI) have remained obscure, partly due to lack of suitable models. When such mice develop advanced coronary atherosclerosis, these stimuli initiate an irreversible endothelin-dependent vasospasm which is later followed by thrombin activation causing coronary thrombosis, irreversible ischaemia and MI (Hemdahl et al 2004). When such mice develop advanced coronary atherosclerosis, these stimuli initiate an irreversible endothelin-dependent vasospasm which is later followed by thrombin activation causing coronary thrombosis, irreversible ischaemia and MI (Hemdahl et al 2004).…”
mentioning
confidence: 99%